2018
DOI: 10.1016/j.jnoncrysol.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Te-As-Se glass destabilization using high energy milling

Abstract: The Te 20 As 30 Se 50 (TAS) glass has been studied under the extreme conditions of high energy milling. Starting from the raw materials, an amorphization process occurs progressively reaching an unstable intermediate state and the final stable state then. Despite its high resistance against crystallization when made using silica tubes, an intermediate state is reached when mechanically alloyed into powder. The evolution of the glass structure has been investigated using Raman spectroscopy and MAS NMR of 77 Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…It can be noticed that this shifted peak is located at the same angle as a diffraction line of the crystallized phase. It could be due (a) to a structural transformation of the initial glass into another polyamorph as already observed in other chalcogenide glasses, 16,17 or (b) to the emergence of nanometric crystalline domains, considering the low stability (T c -T g ) of the glass (~30 K 6 ) where T c and T g are the crystallization and glass transition temperatures, respectively. Other evidences for this glass transformation will be further discussed below.…”
Section: Resultsmentioning
confidence: 75%
“…It can be noticed that this shifted peak is located at the same angle as a diffraction line of the crystallized phase. It could be due (a) to a structural transformation of the initial glass into another polyamorph as already observed in other chalcogenide glasses, 16,17 or (b) to the emergence of nanometric crystalline domains, considering the low stability (T c -T g ) of the glass (~30 K 6 ) where T c and T g are the crystallization and glass transition temperatures, respectively. Other evidences for this glass transformation will be further discussed below.…”
Section: Resultsmentioning
confidence: 75%
“…The results obtained suggest that further research into developing methods of mechanical milling of chalcogenide glasses doped with RE elements and their subsequent sintering using, for example, Spark Plasma Sintering (SPS) technology [9], will make it possible to obtain glasses with significantly increased luminescence efficiency. Based on these glasses, optically active fibers for the IR range can be fabricated.…”
Section: Structure and Optical Propertiesmentioning
confidence: 99%
“…Consequently, the challenge arises from enhancing the homogeneity of RE element distribution within the chalcogenide glass matrix. It was previously shown that chalcogenide glasses can be successfully obtained by the mechanical alloying method from elementary substances [8,9]. This technique has been employed to obtain glassy compositions that are challenging to achieve through conventional melt quenching techniques [10,11].…”
Section: Introductionmentioning
confidence: 99%